The Effect of Group Activity Therapy on Quality of Life and Depression Level in Elderly at Panti Asuhan Yayasan Karya Murni - Yani Lestari; Siska Mariany Ocfica Napitupulu (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
Background and Purpose: Depression and reduced quality of life (QoL) are prevalent but underaddressed conditions among institutionalized elderly. This study aimed to examine the effect of Group Activity Therapy (GAT) on quality of life and depression levels in elderly residents at Panti Asuhan Yayasan Karya Murni, Medan, Indonesia. Methods: A quasi-experimental study with a pre-test–post-test control group design was conducted. Sixty elderly residents (aged ≥60 years) were selected using purposive sampling and equally assigned to intervention (n=30) and control (n=30) groups. Inclusion criteria included residents aged ≥60 years, scoring ≥5 on the Geriatric Depression Scale-15 (GDS-15), and able to communicate. Exclusion criteria included severe cognitive impairment and acute medical illness. The intervention group received eight structured GAT sessions over four weeks (two sessions/week, 60 minutes each), covering music therapy, reminiscence therapy, and light exercise. Quality of life was measured using the validated Indonesian version of the WHOQOL-BREF, and depression was assessed with the GDS-15. Data were analyzed using the Wilcoxon Signed-Rank Test and Mann-Whitney U Test (SPSS v.25, p<0.05). Ethical clearance was obtained from the Institutional Ethics Committee of Universitas Bunda Thamrin (No. 014/EC-UBT/2024). Results: The intervention group showed a significant improvement in QoL (mean pre: 48.3 vs. post: 67.8; p=0.001) and a significant reduction in depression scores (mean pre: 9.7 vs. post: 5.1; p=0.001). The control group showed no significant changes. Between-group comparisons were statistically significant for both outcomes (p=0.001). Conclusion: Group Activity Therapy significantly improves quality of life and reduces depression among institutionalized elderly. Healthcare providers and nursing home administrators should integrate structured group activity programs into routine elderly care to promote psychosocial well-being.